2011
DOI: 10.1186/1743-0003-8-46
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of TMS-induced motor twitch by training is associated with a reduction in excitability of the antagonist muscle

Abstract: BackgroundA single session of isolated repetitive movements of the thumb can alter the response to transcranial magnetic stimulation (TMS), such that the related muscle twitch measured post-training occurs in the trained direction. This response is attributed to transient excitability changes in primary motor cortex (M1) that form the early part of learning. We investigated; (1) whether this phenomenon might occur for movements at the wrist, and (2) how specific TMS activation patterns of opposing muscles unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Our results are consistent with previous data from our laboratory, where twitch direction shifted significantly after training was performed at a distance of 90° away from the baseline twitch direction (Selvanayagam, et al, 2011). While some previous TMS studies, which involved repetitive ballistic thumb movements, reported that twitch directions shifted toward the training direction after 30 minutes of training at 180° away from baseline (Bütefisch et al, 2000;Bütefisch, et al, 2004;Classen, et al, 1998;Giacobbe, et al, 2011;Kaelin-Lang et al, 2005), we showed early neural adaptation occurred with a session of just 40 ballistic wrist contractions at 90° distance away from baseline (Selvanayagam, et al, 2011). The shift in twitch directions is likely to reflect the reweighting of connectivity among the forearm muscles to favour net force production in the training direction (Selvanayagam, et al, 2012a).…”
Section: Post Training Twitches In the Training Posturesupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with previous data from our laboratory, where twitch direction shifted significantly after training was performed at a distance of 90° away from the baseline twitch direction (Selvanayagam, et al, 2011). While some previous TMS studies, which involved repetitive ballistic thumb movements, reported that twitch directions shifted toward the training direction after 30 minutes of training at 180° away from baseline (Bütefisch et al, 2000;Bütefisch, et al, 2004;Classen, et al, 1998;Giacobbe, et al, 2011;Kaelin-Lang et al, 2005), we showed early neural adaptation occurred with a session of just 40 ballistic wrist contractions at 90° distance away from baseline (Selvanayagam, et al, 2011). The shift in twitch directions is likely to reflect the reweighting of connectivity among the forearm muscles to favour net force production in the training direction (Selvanayagam, et al, 2012a).…”
Section: Post Training Twitches In the Training Posturesupporting
confidence: 92%
“…Another consequence of use-dependent learning is demonstrated by a sustained, post-training shift of involuntary (TMS-evoked) twitch direction in the active limb toward the practiced direction (Classen et al, 1998;Giacobbe et al, 2011;van Elswijk et al, 2008).…”
Section: Pg 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if a balance towards UA constriction contributes to the effects observed with rTMS, this would explain a plateauing in MEP GG Amp , because a reduction of excitability seems to occur in the antagonists of a TMS‐targeted muscle (Giacobbe et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The plateauing of inspiratory rTMS GG Amp jointly with the reductions inV I, max and V I suggest that the balance towards constriction is greater during inspiration in comparison to expiration. Moreover, if a balance towards UA constriction contributes to the effects observed with rTMS, this would explain a plateauing in MEP GG Amp , because a reduction of excitability seems to occur in the antagonists of a TMS-targeted muscle (Giacobbe et al 2011).…”
Section: Mechanical Effects Of Rtms On the Uamentioning
confidence: 99%